PENINGKATKAN PEMAHAMAN DAN NILAI MAHASISWA DENGAN METODE PRAKTIKUM - Irwan Ramadhan Ritonga; Dewi Embong Bulan; Mohammad Sumiran Paputungan; Nurfadilah Nurfadilah; Irma Suryana; Adnan Adnan; Iwan Suyatna; Ristiana Eryati; Widya Kusumaningrum; Rani Novia; Ahmad Ahmad; Firman Firman; Andi Fitri Sakmiana (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2023)
Education is one indicator of a country's progress, because it has improved the quality of human resources. One of the Educational activities in the university is joint practicums to improve students' understanding of critical thinking patterns and values. The purpose of this practicum was to examine and analyze the ability of essential patterns of thinking, level of understanding of theory and method, and student learning outcomes as well in the study programme of Marine Science, Mulawarman University. Practicum activities were conducted in Malahing village, Bontang City in November 2022. A total of 52 students took part in the activities. All data in this activity were collected from initial critical thinking skills tests (pre-test) and after (post-test), score from practicum’s report, and participants' perceptual responses in the form of online questionnaires. It was found that the student's critical thinking skills in this activity were in the moderate category based on N-Gains score (0,46). In General, the percentage of understanding and student learning outcomes was in good category (71-84). Based on the student responses, about 92.3% of students were enthusiastic and happy with the practicum learning method. Thus, joint practicum activities might influence increasing student understanding and grades.